ANALISIS YURIDIS NORMATIF SINKRONISASI PERATURAN DAERAH DENGAN HAK ASASI MANUSIA - Muchtar, Henni (Humanus, 2015)
In this reformation era, local administrations need to concern about the recognition and protection of human rights. This article proposed research questions; what kind of bylaws is considered violating human rights from juridical normative view and its synchronization with existing human rights instruments? The above question is based on the idea that in every development plan is not free from public awareness/sense of justice, as well as legal benefit and certainty, which may offend human rights instruments. The research used normative juridical research, which is the method of legal research by researching library materials or secondary materials. This is a normative juridical research on issues concerning the synchronization bylaws with human rights. The research findings based on the study on Pesisir Selatan Regency Regulation No. 8 of 2007 on Nagari Administration, it is not compatible with Human Rights Act No. 39 of 1999. This can be seen from the lack of explicit accommodation on cultural identity of Minangkabau ethnic communities such as indigenous customary court, the function of Kerapatan Adat Nagari, and customary symbols as well as customary title that are overlooked in the regulations. Furthermore, when viewed from the perspective of Civil and Political Rights Act No. 11 of 2005, it is reflected that identity of titles such as titles of tribe, clan, and family is not a concern of the nagari administration. Thus it is a violation of the civil rights of indigenous peoples. Likewise, viewed from the ILO Convention 169 of 1990 on Indigeus Peoples (protection against indigenous peoples), the central government to local administrations must accommodate the interests of indigenous peoples in the state and administration. The separation of the interests indigenous and the nagari government is considered a human rights violation.Keywords: bylaws, human rights, indigenous peoples, nagari